Fuzzy logic based temperature control of thermoelectric cooler (TEC) for single photon avalanche diode (SPAD) application - Samsuddin, Nurul Izzati; Hasbullah, Nurul Fadzlin; Ahmad, Salmiah (2011)
Single photon avalanche diode (SPAD) is a temperature sensitive device. Even a slight variation of temperature can cause unstable performance in quantum efficiency, responsitivity and dark counts. Due to these reasons,unstable temperature could cause overall poor performance of SPAD. It is common for thermoelectric cooler (TEC) to be used as cooling of photodetectors. SPAD was mounted onto the TEC where it needs to be maintained at a constant low temperature under variation of ambient temperature. The system is simulated using Fuzzy Logic Toolbox in MATLAB Simulink. Simulated using P-type fuzzy logic with the set point temperature of 20˚C and ambient temperature of 16˚C, produce a result of -19.44˚C. The P-type fuzzy logic control design has shown a good overall performance where the steady state error is ±0.56˚C, which is equivalent to ±2.8% and the settling time for the output simulation, ts, is 35.91s.